Genzyme : the Renvela launch decision - Calkins, Tim; Harris, Lynn ([London] : SAGE, 2016)
Pharmaceutical company Genzyme has created a new drug, Renvela, which is a phosphate binder designed to be used primarily by patients with kidney failure. Renvela is a slightly different version of Genzyme's highly successful Renagel. Company executives must now decide how best to launch Renvela. Should it replace Renagel? Should it be a premium version of Renagel? Is it worth launching the product at all? This case appears rather simple on the surface, but the questions are challenging to work through.
Originally Published in: Calkins, T., & Harris, L. (2009). Genzyme: The Renvela Launch Decision. 5-308-506. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; New products -- Case studies; Marketing -- Management -- Case studies; Drugs -- Marketing -- Case studies